Study of Oligarchical Performance in Indonesian State-Owned Enterprises: Agency Theory and Javanese Culture Perspectives - Haryani; Syafruddin, Muchamad (Formosa Journal of Sustainable Research, 2024)
This research explores the impact of In a special principal-agent context, Earnings management is used as a mediating variable in the audit quality of oligarchical performance in Indonesian State-Owned Enterprises (ISOE). The Board of Directors, the Board of Commissioners, and the Minister of R.I. are empowered by the State-Owned Enterprises Act. Despite having a significant function, the latter is not granted total authority. The division of power among internal companies, labor unions, the Board of Commissioners, the Minister of R.I., the President of R.I., and political party leaders is a reflection of Javanese culture. The Board of Directors must consider and accommodate all stakeholders, which results in oligarchical performance. An examination of ISOE's 2021 annual reports using partial least squares and WarpPLS 5.0 reveals that earnings act as a mediator between audit quality and oligarchical performance. administration. This study is unique since it is predicated on particular assumptions regarding agency. relationships and Javanese culture in its concept of oligarchical performance and analysis